2015
DOI: 10.1016/j.psychres.2014.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin-induced amelioration of depression-like behaviors in rats by modulating monoamine neurotransmitters in the brain

Abstract: Olfaction plays an important role in emotions in our daily life. Pleasant odors are known to evoke positive emotions, inducing relaxation and calmness. The beneficial effects of vanillin on depressive model rats were investigated using a combination of behavioral assessments and neurotransmitter measurements. Before and after chronic stress condition (or olfactory bulbectomy), and at the end of vanillin or fluoxetine treatment, body weight, immobility time on the forced swimming test and sucrose consumption in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 47 publications
0
38
1
3
Order By: Relevance
“…Vanillin suppresses metastatic potential of human cancer cells via PI3K inhibition, decreases angiogenesis in vivo [26] and exhibits antibacterial and antimicrobial activities [27,28] . The latest research showed that vanillin elevated both serotonin and dopamine levels in brain tissue and could alleviate depressive symptoms in the rat model of chronic depression via the olfactory pathway [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Vanillin suppresses metastatic potential of human cancer cells via PI3K inhibition, decreases angiogenesis in vivo [26] and exhibits antibacterial and antimicrobial activities [27,28] . The latest research showed that vanillin elevated both serotonin and dopamine levels in brain tissue and could alleviate depressive symptoms in the rat model of chronic depression via the olfactory pathway [29] .…”
Section: Introductionmentioning
confidence: 99%
“…This deficit was not fully balanced in the last decades, although some results with the rat experimental model of MDD suggest a possibly efficacy of aromatherapy in MDD. For instance, in a recent publication Xu et al [4] claim that "Our results indicated that vanillin could alleviate depressive symptoms in the rat model of chronic depression via the olfactory pathway. Preliminary analysis of the monoamine neurotransmitters revealed that vanillin elevated both serotonin and dopamine levels in brain tissue.…”
Section: Brain Metabolism and Aromatherapymentioning
confidence: 76%
“…In this paper, we attempt to move one step forward in this line of research, by making a hypothesis that has practical implication for psychotherapy. We restrict our hypothesis to vanillin and citrus fragrances because encouraging experimental results have been found with lemon odors [2,3] and vanillin [4] using the rat model of MDD.…”
Section: Introductionmentioning
confidence: 99%
“…5-HT is closely associated with depression (Cowen, 2008) and previous results showed that vanillin could relieve symptoms of depression in the rat model of chronic depression via increment of serotonin level in the brain (Xu et al, 2015).…”
Section: Article In Pressmentioning
confidence: 94%
“…To achieve this goal, two sets of experiments were conducted: a behavioral study to reveal depression incidence, and a biochemical study to investigate the underlying mechanisms behind anti depression test agent effects. The CMS method is a representative method for the induction of depression in rodents and is similar to the development of stress in humans (Xu et al, 2015).…”
Section: Fig 3 -Effects Of Venlafaxine and Vanillin On The Time Spenmentioning
confidence: 99%